The Analysis of Elements Sportsmanship of the Physical Education Students in the Institute of Physical Education - Piwcram, Pichai; Nilthajan, Nattaya; Piwcram, Maliwan; Sutthipan, Wattana (Academic Journal of Thailand National Sports University, 2018)
The analysis of the elements of sportsmanship of the physical education students in the Institute of Physical Education. The purpose were to analysis elements of sportsmanship of the physical education students in the Institute of Physical Education. The samples used in this research were the undergraduate students in faculty of education in the Institute of Physical Education of the years second to the years five to study in the second semester of the academic years of 2016, The total of 667 persons were choose by Multi – Stage Sampling. The instruments used in data collection were the questionnaire the analysis of the elements of sportsmanship of the physical education students in the Institute of Physical Education. Which were rating scale 5 levels the total of 60 items. It checked the quality of the questionnaire with content validity validation by the experts was the value which were Index of Item Objective Congruence: IOC. It was between 0.67 - 1.00 and the value were Cronbach’s Alpha Coefficient was 0.915. The analysis data by mean and standard deviation of the variables and the analysis element by Principal Component Analysis: PCA, Orthogonal Rotation by Varimax Rotation. The results of this research were as followed : the analysis of the elements sportsmanship of the physical education students in faculty of education in the Institute of Physical Education should include 8 elements such as 1) the courtesy 2) the generosity in working together 3) the honesty, tolerance 4) the acceptance of their abilities and others 5) the discipline 6) the courage 7) the diligence and 8 ) the responsibility.